2016
DOI: 10.5455/ijsm.breastcancer
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Factors Associated With Positive Preoperative Axillary Ultrasound Scanning in Breast Cancer Patients

Abstract: Background: Axillary lymph node status is the most important breast cancer prognostic factor. Preoperative axillary ultrasound examination (PAUS) is used to triage patients for sentinel lymph node biopsy (SLNB) or axillary lymph node dissection (ALND). We assessed the detection rate of lymph node metastases by PAUS in a screening unit and evaluated associations between clinicopathological factors and PAUS positivity. Patients and Methods: This was a single-centre retrospective analysis of data extracted from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Few studies have been conducted to analyze the causes of false-negative results of an ultrasound examination. Jalin's study suggests that the negative results of PAUS study should be evaluated with caution when the tumor is larger (≥ T2), poorly differentiated (G3), or when tumor spreading in blood vessels and lymphatic vessels is detected, as that increases the probability of false-negative results [3]. Nwaugu's study also suggests that the probability of false-negative outcomes increases when the tumor is larger and the tumor spreading in blood vessels and lymph nodes is diagnosed, but the tumor differentiation degree is not statistically significant [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have been conducted to analyze the causes of false-negative results of an ultrasound examination. Jalin's study suggests that the negative results of PAUS study should be evaluated with caution when the tumor is larger (≥ T2), poorly differentiated (G3), or when tumor spreading in blood vessels and lymphatic vessels is detected, as that increases the probability of false-negative results [3]. Nwaugu's study also suggests that the probability of false-negative outcomes increases when the tumor is larger and the tumor spreading in blood vessels and lymph nodes is diagnosed, but the tumor differentiation degree is not statistically significant [15].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in the younger age group with a larger (T2), poorly-differentiated (G3) tumor, and the Volume 12-Issue 5: 2019 9470 detection of tumor spreading in Blood Vessels (V1) and Lymphatic Vessels (L1), the probability of false-negative results is increased; therefore, in these cases, the results of the PAUS study should be evaluated more cautiously. Several studies identified that a heavy nodal disease burden (pN2) and worse prognostic factors of disease (T2, G3, VL1) were detected more frequently in the PAUS-positive group [1,[3][4][5]7,22,24]. Also in our study, in the PAUS-positive group after surgery, a heavy nodal disease burden (pN2) and worse prognostic factors of disease (T2 (p<0.0001), G3 (p=0.034), LV1 (p<0.0001)) were detected more frequently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation